Associations Between Glutathione-S-Transferase Genotypes and Bronchial Hyperreactivity Patients With Di-isocyanate Induced Asthma. A Follow-Up Study - Leppilahti, Jussi; Majuri, Marja-Leena; Sorsa, Timo; Hirvonen, Ari; Piirilä, Päivi (Frontiers in Medicine, 2019)
Introduction Di-isocyanates TDI (toluene di-isocyanate), MDI (diphenylmethane di-isocyanate), and HDI (hexamethylene di-isocyanate) are the most common chemicals causing occupational asthma. Di-isocyanate inhalation has been reported to induce oxidative stress via reactive oxygen and nitrogen species leading to tissue injury. Glutathione transferases (GSTs) and N-acetyltransferases (NATs) are detoxifying enzymes whose general function is to inactivate electrophilic substances. The most important genes regulating these enzymes, i.e., GSTM1, GSTP1, GSTT1, NAT1, and NAT2 represent polymorphic variants resulting enhanced or lowered enzyme activities. Since inability to detoxify harmful oxidants can lead to inflammatory processes involving activation of bronchoconstrictive mechanisms, we studied whether the altered GST and NAT genotypes were associated with bronchial hyperreactivity (BHR) in patients with di-isocyanate exposure related occupational asthma, irrespective of cessation of di-isocyanate exposure and adequacy of asthma treatment. Methods Polymerase chain reaction (PCR) based methods were used to analyze nine common polymorphisms in GSTM1, GSTM3, GSTP1, GSTT1, NAT1, and NAT2 genes in 108 patients with diagnosed occupational di-isocyanate-induced asthma after in mean 11 years (range 1-22 y) of diagnosis. The genotype data were compared with spirometric lung function and BHR status. Results An association between BHR and GSTP1 slow activity (Val105/Val105) genotype was demonstrated in the subjects at the follow-up phase but not at the diagnosis phase. Moreover, the patients with the GSTP1 slow activity genotype exhibited characteristics of Th-2 type immune response more often compared to those with the unaltered GSTP1 gene. Interestingly, all ten patients with the GSTP1 slow activity genotype had both the GSTM3 slow activity genotype and the unaltered GSTT1 gene. Discussion The results suggest associations of the low activity variants of the studied GST genes with BHR. The fact that these associations came up only at the follow-up phase when the subjects were not any more exposed to di-isocyanates, and used asthma medication, suggest that medication and environmental factors influence the presentation of these associations. However, due to the exploratory character of the study and relatively small study size, the findings remain to be confirmed in future studies with larger sample sizes.